2005
DOI: 10.1111/j.1439-0264.2005.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Gastrin‐releasing Peptide, Neuronal Nitric Oxide Synthase and Neurone‐specific Enolase in the Uterus of the North American Opossum, Didelphis virginiana

Abstract: The present study has demonstrated the immunohistochemical localization of gastrin-releasing peptide (GRP), neuronal nitric oxide synthase (nNOS) and neurone-specific enolase (NSE) in the uterus of the North American opossum. Although the presence of GRP, nNOS and NSE has been reported recently in the uterus of eutherian species this is the first description of these peptides in a metatherian species. Metatherian mammals are of interest because in these species it is the prolonged lactation phase of developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…36 Studies on marsupials have detected enolase expression on endothelial cells and have suggested its role in placentation. 37 As a result, anti-α-enolase antibodies may interfere with inflammatory environment in endometrium required for implantation and cause infertility thereby. Although α-enolase is discussed here as an AEA antigen, these antibodies are also involved in systemic autoimmune diseases as well as many inflammatory and degenerative diseases.…”
Section: Antiendometrial Autoantibodies In Its Limited Approachmentioning
confidence: 99%
“…36 Studies on marsupials have detected enolase expression on endothelial cells and have suggested its role in placentation. 37 As a result, anti-α-enolase antibodies may interfere with inflammatory environment in endometrium required for implantation and cause infertility thereby. Although α-enolase is discussed here as an AEA antigen, these antibodies are also involved in systemic autoimmune diseases as well as many inflammatory and degenerative diseases.…”
Section: Antiendometrial Autoantibodies In Its Limited Approachmentioning
confidence: 99%